Social representations and culture an anthropology aproachement (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
In this scientific article offer an introduction to the theory and methodology of social representations from an anthropological perspective, articulating a symbolic concept of culture. Having found little attention in the thesis -in Lima, Peru- motivated me to invite Anthropology students to review and criticize this heuristic proposal with the intention of studying the social thought of social collectivities. It is originally from French Social Psychology, but a central antecedent is the collective representations of Durkheim. SRs contain a symbolic dimension that invites anthropologists to attend to.
Keywords: Anthropology; culture; symbolic dimension and social representations